The Relationship Analysis Between The Index Card Match Learning Model and Students’ Activeness and Memorizing Capability - Jumainah Jumainah; Arman Paramansyah; Yuli Rohmiyati; Yoseb Boari; Nurnaningsih A (Departement of Mathematics Education, 2023)
This study aims to investigate the effects of the Index Card Match learning paradigm on students' attention and memory. This quasi-experimental quantitative study used a non-equivalent group design called pre-test-post-test control group. Students from class X.5 (experimental) and class X.6 (control) served as the study's samples. Tests, surveys, and documentation are utilized as data collection techniques. The independent sample t test was used to analyze the data. Because the t test computation produced a significance value of 0.000, which corresponds to a significance value of 0.005, Ha is accepted whereas Ho is rejected. The N-Gain calculation shows that the learning activity of the experimental class, which is 0.71, falls into the high group, whereas the learning activity of the control class, which is 0.45, goes into the medium category. The N gain memory calculation for the experimental class falls into the middle category at 0.60 and the low category at 0.29 for the control class. The index card match learning paradigm affects the concentration and memory of students.